Epigenetic mechanisms in stem cell therapies for achilles tendinopathy - Yuan, Zheyang; Yao, Zheyu; Mao, Xufeng; Gao, Xiang; Wu, Sengyi; Mao, Haijiao (Frontiers in Cell and Developmental Biology, 2025)
Achilles tendinopathy (AT) is a chronic degenerative tendinopathy that affects people’s daily lives. Multiple clinical studies have found that current conservative treatments fail to promote quality tendon healing. Recent studies have found that stem cell therapy can target pathophysiological changes in the tendon by replenishing tendon-derived cells, promoting extracellular matrix (ECM) remodeling, and modulating the inflammatory response to improve the microenvironment of Achilles tendon regeneration. And epigenetic modifications play an important role in stem cell fate determination and function. In this review, we provided a brief overview of the biological properties of relevant stem cells. The influence of epigenetic modifications on stem cell proliferation, differentiation, and immune regulatory function in the treatment of AT was also explored. We focused on gene regulatory mechanisms controlled by DNA methylation, histones and non-coding RNAs including microRNAs, circRNAs and long non-coding RNAs. We also discuss the current challenges faced by stem cell therapies in treating AT and their potential solutions. Further research in this area will provide a more comprehensive epigenetic explanation for stem cell therapy for AT, leading to the development of stable, safe and effective stem cell therapies.